The Effects of Training Programs, Self-Efficacy, and Work Motivation on Police Officer’s Performance - Pusporini Palupi Jamaludin; Paringsih Paringsih (Politeknik Siber Cerdika Internasional, 2026)
Background: The performance of officers is an important factor in preserving public security and enhancing confidence in the police among communities in Indonesia. The South Tangerang Resort Kepolisian (Police Resort) has been carrying out several reforms related to professional challenges; however, the scope of implementing evidence-based performance improvement strategies still requires broader engagement from academia and practitioners/experts. Objective: This study aimed to analyze the direct and indirect effects of training, self-efficacy, and work motivation on Polri performance in the South Tangerang Police Resort. Methods: A mixed-method sequential explanatory design was used with 208 Non-Commissioned Officer (NCO) personnel from three police sectors, of which 136 respondents were recruited through proportional random sampling. A combination of Likert-scale questionnaires and path analysis supported the quantitative component, while qualitative triangulation employed the Delphi technique. Results: Training, self-efficacy, and work motivation had positive, significant direct effects on performance. Self-efficacy and training were also positively associated with work motivation, which, in turn, partially mediated their relationship with performance, although direct effects were greater than indirect ones. Conclusion: The quality of training, higher self-efficacy through coaching, and motivational systems are needed to optimize performance. In this regard, the present study contributes by providing further confirmation of the mediating role of work motivation in a law enforcement setting.